2019
DOI: 10.3389/fphar.2019.00708
|View full text |Cite
|
Sign up to set email alerts
|

Aliskiren Attenuates the Inflammatory Response and Wound Healing Process in Diabetic Mice With Periodontal Disease

Abstract: The aim of this study was to characterize the role of local RAS (renin–angiotensin system) in the inflammatory response of normal (N) and diabetic (D) mice with periodontal disease (PD). Diabetes Mellitus (DM) was induced by peritoneal injection of streptozotocin in Balb/c mice. PD was induced by ligature around the first molar in both N and D, irrespective of whether they were treated with aliskiren (50 mg/kg, Alisk). Mandibles were harvested for histomorphometric analyses, and gingival tissue (GT) was collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 104 publications
(112 reference statements)
0
31
1
Order By: Relevance
“…The present study results demonstrated that the AT1R blocker, TELM, had a protective effect on PD-induced inflammation and alveolar bone loss in hypertensive animals by decreasing the production of cytokines and reducing the expression of osteoclast markers in hypertensive animals. The action of the local RAS in periodontal tissues has already been described and is associated with periodontal inflammatory damage (Santos et al, 2009;Santos et al, 2015;Dionisio et al, 2019;Oliveira et al, 2019). The SHR strain is known to present alterations in the systemic RAS (Schiffrin et al, 1984;Ohta et al, 1996;Gouldsborough et al, 2003) as well as intrinsic bone impairment associated with the hypertensive genotype and phenotype (Manrique et al, 2012;Landim de Barros et al, 2016;Tiyasatkulkovit et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study results demonstrated that the AT1R blocker, TELM, had a protective effect on PD-induced inflammation and alveolar bone loss in hypertensive animals by decreasing the production of cytokines and reducing the expression of osteoclast markers in hypertensive animals. The action of the local RAS in periodontal tissues has already been described and is associated with periodontal inflammatory damage (Santos et al, 2009;Santos et al, 2015;Dionisio et al, 2019;Oliveira et al, 2019). The SHR strain is known to present alterations in the systemic RAS (Schiffrin et al, 1984;Ohta et al, 1996;Gouldsborough et al, 2003) as well as intrinsic bone impairment associated with the hypertensive genotype and phenotype (Manrique et al, 2012;Landim de Barros et al, 2016;Tiyasatkulkovit et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For IHC analysis, slides were blindly analyzed (n 5/group) in 400× magnification bright-field microscopy (Olympus, BX53, Tokyo, Japan) in the region of interest (middle third of the first molar furcation region), and expression was based on the immunostaining pattern [negative (−); low staining (+); moderate staining (++); strong staining (+++)] (Oliveira et al, 2019). To compose the presented image boards, a representative section was photographed (Olympus, XC50, Tokyo, Japan), in the analyzed region of interest (400× magnification and detailed 1,000× magnification).…”
Section: Immunohistochemical Assays and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…7 Renin can exacerbate the inflammatory response. 11 Therefore, inhibition of renin provides an attractive option for inhibiting the RAAS at its origin. 20 In the present study, aliskiren was able to attenuate the amount of exudate and granuloma formation significantly, in a dosedependent manner, in the cotton-induced granuloma model of inflammation in rats and successfully inhibit paw edema formation in formalin-induced paw edema formation in rats.…”
Section: Discussionmentioning
confidence: 99%
“…10 Aliskiren has been shown to be able to significantly reduce gingival inflammation and enhance wound-healing processes. 11 Another study proved its analgesic and anti-allodynic activity in animal models of pain. 12 These studies demonstrate that aliskiren is a good candidate to be tested for its anti-inflammatory effects.…”
Section: Introductionmentioning
confidence: 99%